2004
DOI: 10.1128/aac.48.6.1968-1973.2004
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-Gallate Enhances the Activity of Tetracycline in Staphylococci by Inhibiting Its Efflux from Bacterial Cells

Abstract: Epigallocatechin-gallate (EGCg), the major catechin present in green tea extracts, has been shown to have several antibacterial activities, limiting bacterial growth and invasion and acting in synergy with ␤-lactam antibiotics. In this article, we report that EGCg at doses half and below its calculated MIC of 100 g/ml, is able to reverse tetracycline resistance in staphylococcal isolates expressing the specific efflux pump Tet(K) and appears to improve the MICs of tetracycline for susceptible staphylococcal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
97
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 204 publications
(104 citation statements)
references
References 21 publications
3
97
0
1
Order By: Relevance
“…1A). The MICs obtained ranged from 125 to 500 mg/ml, similar to that which we reported recently (17); however, they were slightly higher than those already described by other authors (22,24).…”
supporting
confidence: 87%
See 2 more Smart Citations
“…1A). The MICs obtained ranged from 125 to 500 mg/ml, similar to that which we reported recently (17); however, they were slightly higher than those already described by other authors (22,24).…”
supporting
confidence: 87%
“…The first stage, docking, is mainly due to hydrophobic interactions, whereas the next two stages, locking and maturation, are mediated by capsular polysaccharide adhesins, PIA (polysaccharide intercellular adhesin) and PNAG (poly-Nacetylglucosamine polysaccharide), both of which are synthesized by the gene products of the ica operon (icaADBC), with the main contribution coming from an N-acetylglucosaminyltransferase encoded by the icaA gene (5, 12). The expression of the icaA gene alone results in low enzymatic activity, but coexpression with icaD leads to a significant increase in activity (8).Green tea polyphenols and, more specifically, epigallocatechin gallate (EGCg) are known to possess both direct bactericidal activity (18,19) and the ability to potentiate the effects of certain antibiotics (15,16,17,21). Moreover, they have already been shown to have at least an indirect influence on biofilm production, in that they can retard the formation of dental plaque (9,11,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] Various experiments have demonstrated health benefits of green tea catechins against a variety of ailments. [3,[6][7][8][9][10][11][12] Review of English literature has revealed few studies carried out to assess the antifungal effects of green tea active ingredients. There is only one reported study on antifungal effects of green tea extract done on oral samples.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] In addition, the anti-bacterial, antiviral, and antifungal effects of green tea are also being studied. [1,[10][11][12] Many of the health promoting effects of green tea are credited to its polyphenol content and catechins. [13,14] Therefore, the present study was aimed at investigating the antifungal effects of green tea extracts using the active ingredients: 90% polyphenol and 40% epigallocatechin-gallate(EGCG) on oral Candida species in vitro.…”
Section: Introductionmentioning
confidence: 99%